src/HOL/ex/Groebner_Examples.thy
author haftmann
Fri May 07 16:12:26 2010 +0200 (2010-05-07)
changeset 36753 5cf4e9128f22
parent 36724 5779d9fbedd0
child 42463 f270e3e18be5
permissions -rw-r--r--
renamed Normalizer to the more specific Semiring_Normalizer
     1 (*  Title:      HOL/ex/Groebner_Examples.thy
     2     Author:     Amine Chaieb, TU Muenchen
     3 *)
     4 
     5 header {* Groebner Basis Examples *}
     6 
     7 theory Groebner_Examples
     8 imports Groebner_Basis
     9 begin
    10 
    11 subsection {* Basic examples *}
    12 
    13 lemma
    14   fixes x :: int
    15   shows "x ^ 3 = x ^ 3" 
    16   apply (tactic {* ALLGOALS (CONVERSION
    17     (Conv.arg_conv (Conv.arg1_conv (Semiring_Normalizer.semiring_normalize_conv @{context})))) *})
    18   by (rule refl)
    19 
    20 lemma
    21   fixes x :: int
    22   shows "(x - (-2))^5 = x ^ 5 + (10 * x ^ 4 + (40 * x ^ 3 + (80 * x\<twosuperior> + (80 * x + 32))))" 
    23   apply (tactic {* ALLGOALS (CONVERSION
    24     (Conv.arg_conv (Conv.arg1_conv (Semiring_Normalizer.semiring_normalize_conv @{context})))) *})
    25   by (rule refl)
    26 
    27 schematic_lemma
    28   fixes x :: int
    29   shows "(x - (-2))^5  * (y - 78) ^ 8 = ?X" 
    30   apply (tactic {* ALLGOALS (CONVERSION
    31     (Conv.arg_conv (Conv.arg1_conv (Semiring_Normalizer.semiring_normalize_conv @{context})))) *})
    32   by (rule refl)
    33 
    34 lemma "((-3) ^ (Suc (Suc (Suc 0)))) == (X::'a::{number_ring})"
    35   apply (simp only: power_Suc power_0)
    36   apply (simp only: semiring_norm)
    37   oops
    38 
    39 lemma "((x::int) + y)^3 - 1 = (x - z)^2 - 10 \<Longrightarrow> x = z + 3 \<Longrightarrow> x = - y"
    40   by algebra
    41 
    42 lemma "(4::nat) + 4 = 3 + 5"
    43   by algebra
    44 
    45 lemma "(4::int) + 0 = 4"
    46   apply algebra?
    47   by simp
    48 
    49 lemma
    50   assumes "a * x^2 + b * x + c = (0::int)" and "d * x^2 + e * x + f = 0"
    51   shows "d^2*c^2 - 2*d*c*a*f + a^2*f^2 - e*d*b*c - e*b*a*f + a*e^2*c + f*d*b^2 = 0"
    52   using assms by algebra
    53 
    54 lemma "(x::int)^3  - x^2  - 5*x - 3 = 0 \<longleftrightarrow> (x = 3 \<or> x = -1)"
    55   by algebra
    56 
    57 theorem "x* (x\<twosuperior> - x  - 5) - 3 = (0::int) \<longleftrightarrow> (x = 3 \<or> x = -1)"
    58   by algebra
    59 
    60 lemma
    61   fixes x::"'a::{idom,number_ring}"
    62   shows "x^2*y = x^2 & x*y^2 = y^2 \<longleftrightarrow>  x=1 & y=1 | x=0 & y=0"
    63   by algebra
    64 
    65 subsection {* Lemmas for Lagrange's theorem *}
    66 
    67 definition
    68   sq :: "'a::times => 'a" where
    69   "sq x == x*x"
    70 
    71 lemma
    72   fixes x1 :: "'a::{idom,number_ring}"
    73   shows
    74   "(sq x1 + sq x2 + sq x3 + sq x4) * (sq y1 + sq y2 + sq y3 + sq y4) =
    75     sq (x1*y1 - x2*y2 - x3*y3 - x4*y4)  +
    76     sq (x1*y2 + x2*y1 + x3*y4 - x4*y3)  +
    77     sq (x1*y3 - x2*y4 + x3*y1 + x4*y2)  +
    78     sq (x1*y4 + x2*y3 - x3*y2 + x4*y1)"
    79   by (algebra add: sq_def)
    80 
    81 lemma
    82   fixes p1 :: "'a::{idom,number_ring}"
    83   shows
    84   "(sq p1 + sq q1 + sq r1 + sq s1 + sq t1 + sq u1 + sq v1 + sq w1) *
    85    (sq p2 + sq q2 + sq r2 + sq s2 + sq t2 + sq u2 + sq v2 + sq w2)
    86     = sq (p1*p2 - q1*q2 - r1*r2 - s1*s2 - t1*t2 - u1*u2 - v1*v2 - w1*w2) +
    87       sq (p1*q2 + q1*p2 + r1*s2 - s1*r2 + t1*u2 - u1*t2 - v1*w2 + w1*v2) +
    88       sq (p1*r2 - q1*s2 + r1*p2 + s1*q2 + t1*v2 + u1*w2 - v1*t2 - w1*u2) +
    89       sq (p1*s2 + q1*r2 - r1*q2 + s1*p2 + t1*w2 - u1*v2 + v1*u2 - w1*t2) +
    90       sq (p1*t2 - q1*u2 - r1*v2 - s1*w2 + t1*p2 + u1*q2 + v1*r2 + w1*s2) +
    91       sq (p1*u2 + q1*t2 - r1*w2 + s1*v2 - t1*q2 + u1*p2 - v1*s2 + w1*r2) +
    92       sq (p1*v2 + q1*w2 + r1*t2 - s1*u2 - t1*r2 + u1*s2 + v1*p2 - w1*q2) +
    93       sq (p1*w2 - q1*v2 + r1*u2 + s1*t2 - t1*s2 - u1*r2 + v1*q2 + w1*p2)"
    94   by (algebra add: sq_def)
    95 
    96 
    97 subsection {* Colinearity is invariant by rotation *}
    98 
    99 types point = "int \<times> int"
   100 
   101 definition collinear ::"point \<Rightarrow> point \<Rightarrow> point \<Rightarrow> bool" where
   102   "collinear \<equiv> \<lambda>(Ax,Ay) (Bx,By) (Cx,Cy).
   103     ((Ax - Bx) * (By - Cy) = (Ay - By) * (Bx - Cx))"
   104 
   105 lemma collinear_inv_rotation:
   106   assumes "collinear (Ax, Ay) (Bx, By) (Cx, Cy)" and "c\<twosuperior> + s\<twosuperior> = 1"
   107   shows "collinear (Ax * c - Ay * s, Ay * c + Ax * s)
   108     (Bx * c - By * s, By * c + Bx * s) (Cx * c - Cy * s, Cy * c + Cx * s)"
   109   using assms 
   110   by (algebra add: collinear_def split_def fst_conv snd_conv)
   111 
   112 lemma "EX (d::int). a*y - a*x = n*d \<Longrightarrow> EX u v. a*u + n*v = 1 \<Longrightarrow> EX e. y - x = n*e"
   113   by algebra
   114 
   115 end